Hip Screening of a Professional Ballet Company: Using Ultrasound-Assisted Physical Examination Diagnosing the At-Risk Hip. Issue 2 (June 2019) - Rodriguez, Michelle; Bolia, Ioanna K.; Philippon, Michele D.; Briggs, Karen K.; Philippon, Marc J.
The artistic nature of dance in combination with the technical perfection required during performance makes it a highly demanding discipline. Starting at a young age, serious ballet students undergo long hours of training. Professional ballet dancers continue to train intensively in order to maintain their technical proficiency. Hip pathology in ballet dancers has been frequently reported in the literature, including femoroacetabular impingement syndrome, hip instability, muscle injuries, and early osteoarthritis. Screening programs to identify these hip joint pathologies (atrisk hips) in ballet dancers when they are still asymptomatic or their injury does not affect their performance are useful to aid in the development of prevention and treatment strategies. The purpose of this cross-sectional study was to identify hips at risk in the members of a professional ballet company using ultrasoundassisted physical examination. A high prevalence of cam lesions was detected in this cohort. Dancers with cam lesions were more likely to have an acetabular labral tear. In addition, there was a positive correlation between cam lesions and Abstract The artistic nature of dance in combination with the technical perfection required during performance makes it a highly demanding discipline. Starting at a young age, serious ballet students undergo long hours of training. Professional ballet dancers continue to train intensively in order to maintain their technical proficiency. Hip pathology in ballet dancers has been frequently reported in the literature, including femoroacetabular impingement syndrome, hip instability, muscle injuries, and early osteoarthritis. Screening programs to identify these hip joint pathologies (atrisk hips) in ballet dancers when they are still asymptomatic or their injury does not affect their performance are useful to aid in the development of prevention and treatment strategies. The purpose of this cross-sectional study was to identify hips at risk in the members of a professional ballet company using ultrasoundassisted physical examination. A high prevalence of cam lesions was detected in this cohort. Dancers with cam lesions were more likely to have an acetabular labral tear. In addition, there was a positive correlation between cam lesions andpositive dial test, which is an indication of hip microinstability. Work of this kind can help to improve understanding of hip pathology in dancers and facilitate activity modification programs to prevent progression of their hip injuries.